2010
DOI: 10.1029/2009ja014502
|View full text |Cite
|
Sign up to set email alerts
|

Detection of terrestrial gamma ray flashes up to 40 MeV by the AGILE satellite

Abstract: [1] We report the detection by the Astrorivelatore Gamma a Immagini Leggero (AGILE) satellite of terrestrial gamma ray flashes (TGFs) obtained with the minicalorimeter (MCAL) detector operating in the energy range 0.3-100 MeV. We select events typically lasting a few milliseconds with spectral and directional selections consistent with the TGF characteristics previously reported by other space missions. During the period 1 June 2008 to 31 March 2009 we detect 34 high-confidence events showing millisecond durat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
210
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 205 publications
(219 citation statements)
references
References 35 publications
3
210
0
3
Order By: Relevance
“…They were first observed in 1994 from the Compton Gamma‐ray Observatory satellite (Fishman et al, 1994) and later confirmed by other space‐based observations (Briggs et al, 2010; Marisaldi et al, 2010; Smith et al, 2005). X‐rays have also been observed at closer proximity to the source with sensors on the ground and on balloons (Dwyer, 2004; Mallick et al, 2012; Moore et al, 2001) and in high‐voltage laboratory discharge experiments of long sparks (Babich et al, 2015; Dwyer et al, 2005; Kochkin et al, 2014, 2016).…”
Section: Introductionmentioning
confidence: 69%
“…They were first observed in 1994 from the Compton Gamma‐ray Observatory satellite (Fishman et al, 1994) and later confirmed by other space‐based observations (Briggs et al, 2010; Marisaldi et al, 2010; Smith et al, 2005). X‐rays have also been observed at closer proximity to the source with sensors on the ground and on balloons (Dwyer, 2004; Mallick et al, 2012; Moore et al, 2001) and in high‐voltage laboratory discharge experiments of long sparks (Babich et al, 2015; Dwyer et al, 2005; Kochkin et al, 2014, 2016).…”
Section: Introductionmentioning
confidence: 69%
“…Concerning the maximal energy, the original BATSE detection of TGFs up to a few MeV [1,9] was superseded by the RHESSI detection up to 20 MeV [2,10]. Recently, the AGILE satellite showed that TGF spectrum extends well above 20 MeV [11] (Tavani et al, 2009, submitted to Nature), as confirmed also by the Fermi-GBM detector [12].…”
mentioning
confidence: 95%
“…This may be due to a difference in atmospheric density at ground and high mountains. In fact, a TGF spectrum on average extends to a few tens of MeV [38,39], or 100 MeVon rare occasions [36]. It is believed that TGFs occur at altitudes of 15-20 km [40].…”
Section: Characteristics Of -Ray Emissionsmentioning
confidence: 99%